Abnormal Agitated Saline Study Results after Tetralogy of Fallot Repair. Issue 10 (15th September 2013) - Tunks, Robert D.; Barker, Piers C.A.; Johnson, Jason N.; Campbell, Michael J.
<x xml:space="preserve">Abstract</x> Residual intracardiac or extracardiac shunting is frequently seen in patients with repaired congenital heart disease and can cause systemic hypoxemia. We present the case of an adult with tetralogy of Fallot who underwent two corrective surgical procedures as a child with subsequent pulmonary valve replacement due to residual pulmonary insufficiency. Further details of her operative history were otherwise unknown. After being lost to follow‐up for many years, she presented with unexplained cyanosis and a markedly abnormal agitated saline study on transthoracic echocardiography in which only the left heart filled after contrast administration. We review the differential diagnosis for such a presentation and discuss the utility of cardiac magnetic resonance imaging (MRI) to define the etiology. Cardiac MRI, a frequently used imaging modality to longitudinally assess adult patients with congenital heart disease, provides excellent image quality of cardiac structures and the ability to perform angiography in a variety of imaging planes. These advantages render cardiac MRI, a useful modality to determine the etiology of unexplained cyanosis in these patients as both intracardiac and extracardiac shunts can be detected.